The glasses II [videorecording (DVD)] - Bligh, James; Bermender, Shawna; Smalls, Kwame (360 Sound and Vision Entertainment, 2014)
An art buyer acquires a pair of sunglasses that gives him the ability to scope out the finest art, until his own fate catches up to him.